(untitled) (MAUSAM, 1978)
During the Indo-Soviet Monsoon Experiment (ISMEX) .973, closely spaced aerological measurements were obtained in the west Indian Ocean and the Arabian Sea. Based on these observations a study of the thermodynamical and kinematic structure of the atmospheric planetary boundary layer in this region is made. Under undisturbed weather conditions the planetary boundary layer is mainly divided into two sub-layers-the neutral stratified mixed layer and the cloud layer. In the region north of 10°N latitude over the Arabian Sea, a strong temperature inversion tops the boundary layer and shows a downward slope from the coast of India towards the west, thus reducing the planetary boundary layer in the western region to a mixed layer and a temperature inversion layer. In the extreme eastern region, strong convective mixing weakens the layered structure and leads to the destruction of the inversion. A gradual increase of wind speed with height is observed in the sub-cloud layer in this region. A sharp maximum frequently occurs below 1200 m in the wind profiles in the region north of 7°N latitude over the Arabian Sea. The wind speed maximum occurs usually within the inversion layer in the western Arabian Sea and within the cloud layer in the central Arabian Sea, and is often associated with large values of wind shear at low levels.